Treatment of produced water in a floating carrier bioreactor - Ezechi, E.H. (Korean Society of Environmental Engineers, 2017)
Produced water is the largest wastestream of oil and gas exploration. It consists of various organic and inorganic compounds that hinder its beneficial use. This study compared the treatment of produced water in a batch suspended and biofilm activated sludge process. The biofilm carrier material was made from Gardenia Carinata shell. COD, NH4 +-N and NO3-N removal was monitored in both the suspended (control) and floating carrier bioreactors. The results show a rapid reduction of produced water constituents in the floating carrier bioreactor. COD, NH4 +-N and NO3-N removal was in the range of 99, 98 and 97 for the floating carrier bioreactor whereas it was 88, 84 and 83 for the control bioreactor. The rapid reduction of COD, NH4 +-N and NO3-N clearly indicate that the floating carrier materials served as an attached growth medium for microorganisms, improved the breakdown of produced water constituents and reduced inhibition of microbial metabolic activities. © 2017 Korean Society of Environmental Engineers.